Seroprevalencia de brucella abortus y ocurrencia de brucella melitensis en caprinos y en ovinos de Cesar y Sucre (2010)
Brucella melitensis is the main causative agent of brucellosis in goats and sheep. In Colombia, seropositives against B. mellitenses has not been detected, therefore, it is important to carry out an active surveillance in these two animal groups that could be susceptible to B. mellitenses or other Brucella species. The aim of this study was to determine the seroprevalence of B. melitensis and of B. abortus in goats in the municipalities of Valledupar (Cesar) and sheep in the municipality of Coloso (Sucre). A prospective study of cross-section that included a total of 329 animals, goats and sheep, was performed. In the municipality of Valledupar 209 goats were sampled, belonging to ten farms and the municipality of Coloso 120 sheep within the four farms. Serologic diagnosis was performed by the technique of rapid agglutination in plate Rose Bengal and indirect ELISA for goats and sheep. This study allowed to estimate seroprevalence to B. abortusof 1.2% (4/329) by the technique of Rose Bengal, these sera were confirmed by competitive ELISA, detecting negative results. The seroprevalence of B. melitensis was 0%, thereby allowing to extrapolate a limited risk and agrees with the notification never made in Colombia. These findings confirm the importance of active surveillance in these two susceptible species.